Molecular characterization of Cyclophilin (TcCyP19) in Trypanosoma cruzi populations susceptible and resistant to benznidazole - Rêgo, Juciane Vaz (2015)
Fil: Rêgo, Juciane Vaz. Universidade Federal do Piauí. Campus Amilcar Ferreira Sobral; Brasil.